Skeletal muscle glycogen loss evoked by resistance exercise - Tesch, P. A.; Ploutz-Snyder, L. L.; Ystrom, L.; Castro, M. J.; Dudley, G. A (The Journal of Strength and Conditioning Research, 1998)
Biopsies were taken from the left m. vastus lateralis of 9 young men and analyzed for mixed muscle and for single fiber glycogen to infer recruitment, especially among fast-twitch subtypes, during knee extensions with loads of 30,45, and 60% of 1-repetition maximum. The relative decline in mixed muscle glycogen was related to relative exercise load, as were the percentage of fast-twitch fibers showing glycogen loss and the relative cross-sectional area (CSA) of m. vastus lateralis occupied by type IIa or by fast-twitch fibers that showed glycogen loss (p 0.0478, r 0.50). The relative decline in mixed m. vastus lateralis glycogen was related to the percentage of both fast-twitch fibers and type IIa fibers, and the relative CSA of m. vastus lateralis occupied by type IIa fibers that showed glycogen loss (p 0.0436, r 0.51). Type I and IIa fibers were used for all 3 bouts. Type IIab + IIb fibers showed glycogen loss for the heaviest load. The results suggest that mixed muscle glycogen loss is related to load, mainly due to fast fi ber usage. It also appears that the general understanding put forth for cycling and running—that fast-twitch fiber type use depends on exercise intensity—holds for resistance exercise. Because type IIab + IIb fibers showed glycogen loss at loads of 60% of maximum, it is suggested that fast-twitch subtypes are used at lower loads than generally appreciated.